Key factors affecting purchase intention in Russian online context - Kozlova, Olessia (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Russian e-commerce has drawn a lot of attention in academic publications as well as in public media lately. The market is growing with a speed of rocket offering companies enormous business opportunities. However, combination of Russian culture, consumer online purchasing and decision-making process forms a subject yet completely unknown. From international online business perspective it is vital for companies to know how a culture affects consumer’s purchase decision and what are the key elements that need to be modified in order to successfully expand online operations to Russian market. Here, the main purpose is to define the key factors affecting Russian consumer’s online purchase intention. In order to answer the main research question, firstly the role of culture in purchase intention context is researched. Secondly, focus is drawn to the factors that affect online purchase intention. Lastly, it is researched how Russian culture is affecting e-commerce attributes modification. The objective is not only to expand the theoretical understanding of the subject but also to provide companies with a clear vision on how the online operations should be conducted in Russian online market. Ranganathan’s and Jha’s conceptual framework was chosen as a ground theory in this study. Here, three main categories Computer Self-Efficacy and Past Online Experience, Website Quality and Costumer Concerns form basis for the study. Various articles and academic literature supplemented this theoretical approach. Qualitative research method was adapted and the study was conducted through five expert interviews. As a conclusion it can be stated that culture forms a ground for entire purchase decision-making process in online context. Results from the interviews were grouped according to main three theoretic categories and placed with Ranganathan’s and Jha’s original framework. This formed a new theoretical framework that defines diverse factors affecting specifically Russian consumer’s online purchase intention. This study suggests that following factors need to be taking into serious consideration in Russian online context: photography style, detailed product and company information, colors, language, product variety, reviews, recommendations, strong social media presence, fast check out and minimalistic order information, counterfeit fear, cash on delivery payment, training and guidance, extensive customer service, consumers’ insecurity, inexperience, high interest for technology and their individualistic personality.